2002
DOI: 10.1034/j.1600-0447.2002.1o267.x
|View full text |Cite
|
Sign up to set email alerts
|

Public attitude to compulsory admission of mentally ill people

Abstract: The mostly positive attitude to compulsory admission suggests that the public trust in psychiatry to deal with the assigned responsibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
6

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 21 publications
2
42
0
6
Order By: Relevance
“…C ontrasting results about the importance of stigma for persons with mental illness are reported in research literature: several studies in the United States and in other Western nations on public attitudes have shown that people with mental illness are met with a great amount of rejection and social distance (Brockington et al, 1993;Lauber et al, 2000Lauber et al, , 2002aLauber et al, , 2004Link et al, 1992). However, other analyses found that public attitudes toward mentally ill people were not necessarily unfavorable (Gove, 1982;Huffine and Clausen, 1979).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…C ontrasting results about the importance of stigma for persons with mental illness are reported in research literature: several studies in the United States and in other Western nations on public attitudes have shown that people with mental illness are met with a great amount of rejection and social distance (Brockington et al, 1993;Lauber et al, 2000Lauber et al, , 2002aLauber et al, , 2004Link et al, 1992). However, other analyses found that public attitudes toward mentally ill people were not necessarily unfavorable (Gove, 1982;Huffine and Clausen, 1979).…”
mentioning
confidence: 89%
“…The community sample is drawn from a representative population survey in Switzerland on public attitudes toward mental illness and the institutions involved (Lauber et al, 2000(Lauber et al, , 2002a(Lauber et al, , 2002b(Lauber et al, , 2003(Lauber et al, , 2004. Inclusion criteria for this representative survey were age between 16 and 76 years, living in a private household, and having a telephone.…”
Section: Community Samplementioning
confidence: 99%
“…A study of the public's attitudes to compulsory treatment of the mentally ill in Switzerland indicated a high level of trust in psychiatrists (27).…”
Section: Evidence For Trustmentioning
confidence: 99%
“…Second, a vignette depicting a person with either major depression or schizophrenia fulfilling the respective DSM-III-R criteria was presented. Third, different variables including demographic factors (such as age, gender, education, profession) were assessed: negative emotions (Lauber et al, 2000a; Cronbach's : 0.73) and social distance towards the case presented (Lauber et al, 2004;Cronbach's : 0.85), participation in community activities (Lauber et al, 2002a; Cronbach's : 0.74), rigidity of interviewees (Lauber et al, 2002b; Cronbach's : 0.62) and stereotypes (Lauber et al, 2000a; Cronbach's : 0.50) held by the interviewees, and, finally, contact with mentally ill people (Lauber et al, 2003;Cronbach's : 0.49). Stereotypes are the mentally ill's assumed characteristics compared with the normal population.…”
Section: The Interviewmentioning
confidence: 99%